Atomization of a liquid jet in supersonic crossflow in a combustion chamber with an expanded section. (March 2021) - Zhao, Jiafeng; Ren, YongJie; Tong, Yiheng; Lin, Wei; Nie, Wansheng
Abstract: The diffusion process and spatial distribution of a liquid jet in supersonic crossflow (Mach number of 2) in a model combustor with an expanded section were investigated on the basis of experiments and simulations. Experiments were performed using high-speed photography, high-speed shadowgraph and laser-based particle size analyzer to investigate the spray structures, flow fields and droplet diameter, respectively. The Eulerian-Lagrangian method coupled with the Kelvin-Helmholtz/Rayleigh-Taylor breakup model were used in the simulations. Moreover, delayed detached eddy simulation numerical method based on the two-equation shear stress transport turbulence model was applied. The spray distributions and flow fields predicted in the simulation, including the spray penetration, cross-sectional distribution, droplet size in the far-field, the bow shock, large-scale vortices and recirculation zones were in good agreement with experiments. The evolution of spray in supersonic crossflow could be divided into three stages, aerodynamic induced liquid column fracturing, expansion wave promoted spray accelerating, and compression wave disturbed spray blending. Overall, the channel configuration (with expended section) changed the direction and strength of the supersonic airflow. The force of the crossflow determined the spray diffusion. Highlights: The diffusion process and spatial distribution of LJISC in a combustor with an expanded section were investigated. The simulation results such as spray structures, airflow structures were comprehensively verified experimentally. Typical structures of LJISC in a rectangular channel with an expaned section could be divided into three regions.